SnO2 nanocrystals synthesized by microwave-assisted hydrothermal method: towards a relationship between structural and optical properties - Mendes, Paulo G.; Moreira, Mario L. [UNESP]; Tebcherani, Sergio M.; Orlandi, Marcelo Ornaghi [UNESP]; Andres, J.; Li, Maximu S.; Diaz-Mora, Nora; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Springer, 2012)
The exploration of novel synthetic methodologies that control both size and shape of functional nanostructure opens new avenues for the functional application of nanomaterials. Here, we report a new and versatile approach to synthesize SnO2 nanocrystals (rutile-type structure) using microwave-assisted hydrothermal method. Broad peaks in the X-ray diffraction spectra indicate the nanosized nature of the samples which were indexed as a pure cassiterite tetragonal phase. Chemically and physically adsorbed water was estimated by TGA data and FT-Raman spectra to account for a new broad peak around 560 cm(-1) which is related to defective surface modes. In addition, the spherical-like morphology and low dispersed distribution size around 3-5 nm were investigated by HR-TEM and FE-SEM microscopies. Room temperature PL emission presents two broad bands at 438 and 764 nm, indicating the existence of different recombination centers. When the size of the nanospheres decreases, the relative intensity of 513 nm emission increases and the 393 nm one decreases. UV-Visible spectra show substantial changes in the optical absorbance of crystalline SnO2 nanoparticles while the existence of a small tail points out the presence of localized levels inside the forbidden band gap and supplies the necessary condition for the PL emission.
Keywords: SnO2; Nanoparticles; Microwave-assisted hydrothermal; Luminescence; Quantum confinement